Testing the Fertilizer Effect of Compost Produced by Anaerobic Fermentation of Sewage Sludge - Benoni Lixandru (Scientific Papers Animal Science and Biotechnologies, 2010)
The compost tested in this study resulted from the anaerobic fermentation process of sewage sludge with cereal straw. Processing and post-treatment were made by Biotechnological Research Centre within INCD ECOIND from Bucharest. Experimental program included testing the effect of fertilizer in quantities of 25 t, 50 t and 100 t compost / ha on the production of soya beans. It was also investigated the influence of the combination of fertilization with compost and inorganic fertilization with levels of 200 kg, respectively, 400 kg NPK / ha. Was analyzed the following productivity indicators: plant density, number of floors of pods, number and weight of pods and total beans production, in full ripening stage. In the case of fertilization only with composted sludge, production of peas and beans was higher in variants with 50 t / ha and 100 t / ha (2095 kg and 1990 kg grain / ha). Therefore, doubling the amount of compost does not provide corresponding increase yields of soybeans. Combining organic and inorganic fertilization determine a proportional production increase only for the total biomass production. The tested compost is a good organic fertilizer and the amount that provides the greatest soybeans production is 50 t / ha.